2013
DOI: 10.3892/etm.2013.1406
|View full text |Cite
|
Sign up to set email alerts
|

Combination of hearing screening and genetic screening for deafness-susceptibility genes in newborns

Abstract: The aim of this study was to determine the clinical significance of the results of screening of newborn hearing and the incidence of deafness-susceptibility genes. One thousand newborn babies in the Handan Center Hospital (Handan, China) underwent screening of hearing and deafness-susceptibility genes. The first screening test was carried out using otoacoustic emissions (OAEs). Babies with hearing loss who failed to pass the initial screening were scheduled for rescreening at 42 days after birth. Cord blood wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In contrast to previous studies that reported only cross-sectional or short-term observations of newborn genetic screening for deafness, [16][17][18] the strength of this study lies in that we prospectively performed comprehensive, long-term audiometric evaluations up to 6 years in babies with conclusive genotypes. These long-term observations are valuable in delineating the clinical features of the corresponding mutations.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In contrast to previous studies that reported only cross-sectional or short-term observations of newborn genetic screening for deafness, [16][17][18] the strength of this study lies in that we prospectively performed comprehensive, long-term audiometric evaluations up to 6 years in babies with conclusive genotypes. These long-term observations are valuable in delineating the clinical features of the corresponding mutations.…”
Section: Discussionmentioning
confidence: 57%
“…15 Our findings concerning the feasibility and prognostic value of newborn genetic screening were subsequently validated in several studies. [16][17][18] However, implementing population-wide genetic screening for deafness involves multiple issues and demands careful appraisal with regard to the potential psychosocial impacts on families and economic burden on the healthcare system. Longitudinal follow-up and analyses of clinical outcomes in newborns who screened positive for deafness mutations are necessary to address these issues.…”
Section: Introductionmentioning
confidence: 99%
“…According to a survey from the World Health Organization (WHO) in 2013, there are ~360 million people with varying degrees of deafness worldwide (2). According to epidemiological data, ~1 in 1,000 newborns is diagnosed with congenital deafness (3). Deafness directly affects cognition, thinking and memory, resulting in a decline in the quality of life, thereby contributing to the burden of families and society (4).…”
Section: Introductionmentioning
confidence: 99%
“…The deafness genes including GJB2, GJB3 and SLC26A4 are mainly autosomal recessively inherited, while 12SrRNA is maternally inherited (18,19). Detection of deafness couples and parents of patients with mutations in GJB2, SLC26A4 and 12SrRNA genes were performed to determine the genotypes and estimate recurrence risk on the basis of genotypes.…”
Section: Discussionmentioning
confidence: 99%